Depressão, ansiedade, qualidade de vida e estratégias de enfrentamento após transplante cardíaco - Trevizan, Fulvio Bergamo (2016)
Heart transplantation is the therapeutic procedure indicated to increase the survival of patients with refractory heart failure. Improvement in overall functioning and quality of life are expected factors in the postoperative period. Objectives: To identify and evaluate mental disorders and symptoms, such as depression and anxiety, quality of life and coping strategies in the post-surgical situation of heart transplantation, as well as to correlate the variables and comparing them between sex, age group and time after transplantation. Method: A cross-sectional, quantitative study with patients who have undergone heart transplantation at Hospital de Base of São José do Rio Preto, SP. Participants answered to the Sociodemographic Questionnaire, the Beck Depression Inventory (BDI-II), Beck Anxiety Inventory (BAI), the MINI International Neuropsychiatric Interview, the Ways of Coping Scale (EMEP) and WHOQOL-BREF, World Health Organization to assess quality of life. For data analysis, the significance level was considered P≤0.05. Results: A total of 33 patients participated in the study, 67% (n=22) males, mean age 52 years (± 11.75), mean time after transplantation 10 years (± 3.39). Female patients were 33% (n=11), mean age 54 years (± 11.04), mean time of transplantation 10 years (± 3.28). The BDI-II results indicated that 91% (n=30) presented a minimal level, 6% (n=2) mild level and 3% (n=1) moderate level of depression symptoms. In BAI, 94% (n=31) demonstrated minimal level, 3% (n=1) mild level and 3% (n=1) moderate level of anxiety symptoms. WHOQOL-BREF showed a perception of quality of life considered good (60-80 points) in all domains: psychological (70.45), social relationship (69.7), environment (67.33) and physical (63.53). The EMEP data have registered a problem-focused coping strategy (M=3.56 ± 0.68), religiosity (M=3.55 ± 0.48), social support (M=3.34 ± 0.73) and emotion M=1.76 ± 0.36). According to MINI, a single case of major depressive episode, current and recurrent was recorded. Significant differences were found in the perception of the psychological domain of men as being higher than in women (P=0.0071). Men were more satisfied with the environment (P=0.0387); patients aged ≥ 53 years focusing more on religiosity for coping with problems than lower-aged patients (P=0.039), which was also their main strategy. Conclusion: Although most participants in the sample had symptoms of depression and anxiety, only one patient was identified with moderate symptoms in both domains. The most used strategy was coping problem-focused, followed by focusing on religiosity, social support and emotion. Patients have classified the perceptions of quality of life as 'good', pointing out satisfaction with their health.